Investigation of base flow for an axisymmetric suddenly expanded nozzle with micro JET - Chaudhary, Zakir Ilahi; Shinde, Vilas B.; Khan, Sher Afghan (Science Publishing Corporation, 2018)
This investigation presents the outcome of the tests conducted to control the pressure in the re-circulation zone. Also, the efficiency of the flow controllers to govern the pressure at the base in a rapidly expanded pipe has been investigated. Tiny jets our in number of 1 mm diameter are positioned at the interval of 90 degrees at 6.5 mm from the central axis of the main jet. The Mach numbers of the abruptly expanded flows studied for base pressure range from 1.1 to 3 and the obtained wall pressure distribution is depicted for Mach number 1.6 and 1.8 respectively. Axi-symmetric round brass tubes were used to join jets; and cross-sectional area of those tubes are 2.56. L/D ratio of the broadened pipe was differed from 1 to 10 and NPR was shifted from 3 to 11. Notwithstanding, the outcomes displayed were for Low L/D values of 4, 3, 2 and 1 individually. Also, when the stream was released to the pipes of the given area ratios, it stayed connected with the channel divider for all the inertial levels and the NPRs tried in the present case. Further it is understood that level of expansion assumes a noteworthy part to choose the pressure at the base and its control adequacy. At whatever point, the stream is over expanded, it leads to the formation of an oblique shock at the nozzle lip, prompting improvement of the pressure in the base locale. Shock waves formation, reflection and recombination proceeded till the pressure winds up noticeably environmental and seen that the stream stays intact for low L/D ratio of 4. Very small scale (micro) jets proved to fit in as controllers for the base pressure.